Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\left(-4\right).\left(-3\right).25.\left(-8\right)\)
\(=12.25.\left(-8\right)\)
\(=12.\left(-200\right)\)
\(=-2400\)
\(b,7.\left(-25\right).\left(-3\right)^2.\left(-4\right)\)
\(=7.\left(-3\right)^2.100\)
\(=7.9.100=63.100\)
\(=6300\)
\(d,\left[93-\left(20-7\right)\right]:16\)
\(=\left[93-13\right]:16\)
\(=80:16=5\)
\(e,51-\left(-51\right)+\left(-53\right)+49\)
\(=51.2-53+49=102-53+49\)
\(=49.2=98\)
\(f,168-49+\left(-68\right)+4\)
\(=168-68-49+4=100-45=55\)
\(g,53-\left(-7\right)+\left(-53\right)-49\)
\(=53+7-53-49\)
\(=7-49=-42\)
\(h,25.\left(-124\right)+124.25\)
\(=25.\left(-124+124\right)\)
\(=25.0=0\)
\(i,\left(-11\right).36-64.11\)
\(=11.\left(-36\right)+\left(-64\right).11\)
\(=11.\left(-36-64\right)=11.\left(-100\right)\)
\(=-1100\)
\(k,125.\left(-24\right)+24.125\)
\(=125.\left(-24+24\right)=125.0=0\)
\(l,125.\left(-23\right)+23.\left(225\right)\)
\(=-125.23+23.225\)
\(=23.\left(-125+225\right)=23.100=2300\)
\(m,-11.36+64.\left(-11\right)\)
\(=-11.\left(36+64\right)=-11.100=-1100\)
Bài 1:
a) Ta có: 49+(11-25)
=49+11-25
=24+11
=35
b) Ta có: \(-8+5\cdot\left(-9\right)\)
\(=-8-45\)
=-53
Bài 2:
a) Ta có: \(x-2=-6+17\)
\(\Leftrightarrow x-2=11\)
hay x=13
Vậy: x=13
b) Ta có: \(x+9=2-17\)
\(\Leftrightarrow x+9=-15\)
hay x=-24
Vậy: x=-24
a,
= 4.3.25.8
= (4.25).3.8
= 100.24
= 2400
b,
= 7.25.3.3.4
= (25.4).7.3.3
= 100.63
= 6300
d,
= (93-13):16
= 80:16
=5
e,
= 53+51-53+49
= (53-53)+(51+49)
= 0+100
= 100
f,
= 168-49-68+4
= (168-68)+4-49
= 0+4-49
= -45
g,
= 53+7-53-49
= (53-53)+7-49
= 0+7-49
-42
h,
= (-25).124+124.25
= 124.(25-25)
= 124.0
= 0
i,
= 11.(-36)-64.11
= 11.(-36-64)
= 11.(-100)
= -1100
k,
= 125.(24-24)
= 125.0
= 0
l,
= (-125).23+23.225
= 23.(225-125)
= 23.100
= 2300
m,
= (-11).(36+64)
= (-11).100
= -1100
a) (-4).(-3).25.(-8)
= (-4.25).[(-3).(-8)]
=-100.24
=-2400
b) 7.(– 25).(– 3)2.(– 4)
= 7.(-25).9.(-4)
=(7.9).[(-25).(-4)]
=63.100
=6300
d)[ 93–( 20–7 )]:16
= [ 93 - 13]:16
= 80 : 16
= 5
e) 53 – (–51) + (-53) + 49
= 53 + 51 + (-53) + 49
= [53+(-53)] + (51+49)
=0 + 100
=100
f) 168 – (49) + (-68) + 4
= [168+(-68)] + 4 - 49
= 100 + 4 - 49
= 104 - 49
= 55
g) 53 – (–7) + (-53) – 49
= 53 + 7 - 53 - 49
= (53 - 53) + (7 - 49)
= 0 + ( - 42)
= -42
h) 25.(- 124) + 124. 25
= 25.(-124+124)
= 25.0
=0
i) (-11).36 - 64.11
= 11.(-36-64)
= 11.(-100)
= -1100
k) 125.(- 24) + 24.125
=125.(-24+24)
=125.0
=0
l) 125.(-23) + 23.225
=23.(-125+225)
=23.100
=2300
m) (-11).36 + 64.(- 11)
=(-11).(36+64)
=-11.100
=-1100
a. \(9900:36-15\cdot11\)
\(=275-15\cdot\left(10+1\right)\)
\(=275-150-15\)
\(=125-15\)
\(=110\)
b. \(\left(15792:336\right)\cdot5+27\cdot11\)
\(=47\cdot5+27\cdot\left(10+1\right)\)
\(=235+270+27\)
\(=532\)
\(\left(-12\right)+\left(-13\right)+36+\left(-11\right)\)
\(=\left(\left(-12\right)+\left(-13\right)+\left(-11\right)\right)+36\)
\(=\left(-12-13-11\right)+36\)
\(=-36+36\)
\(=0\)
( - 12 ) + ( - 13 ) + 36 + ( - 11 )
= 36 + [ (-12) + ( - 13 ) + ( -11 )]
= 36 + ( - 36 )
= 0
(-12)+(-13)+36+(-11)
= -12 - 13 + 36 - 11
= - (11+12+13) + 36
= - 36 + 36
= 0
Giải
a)-5/18+5/9-11/36
=(-10/36)+20/36-11/36
=-1/36
b)-39/44:13/11
=-39/44.11/13
=-3/4
a) \(\frac{-5}{18}+\frac{5}{9}-\frac{11}{36}\)
= \(-\frac{10}{36}+\frac{20}{36}-\frac{11}{36}\)
= \(-\frac{1}{36}\)
b) \(-\frac{39}{44}:\frac{13}{11}\)
= \(-\frac{39}{44}.\frac{11}{13}\)
= \(\frac{\left(-39\right).11}{44.13}\)
= \(\frac{\left(-3\right).13.11}{11.4.13}\)
= \(-\frac{3}{4}\)